2006
DOI: 10.2514/1.17459
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady and Transitional Flows Behind Roughness Elements

Abstract: The role of surface roughness in boundary layers continues to be a topic of significant interest, especially with regard to how controlled roughness might be used to delay laminar-to-turbulent transition. Although it may be useful for control, large-amplitude roughness may itself lead to transition. In an effort to understand the breakdown mechanics associated with large-amplitude surface roughness, experiments are conducted to investigate the steady and unsteady disturbances generated by three-dimensional rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
114
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 29 publications
(45 reference statements)
11
114
1
Order By: Relevance
“…The value of Re h has an important effect on the streak amplitude, length scales and perturbation growth rate (Choudhari & Fischer 2005;Ergin & White 2006;Denissen & White 2008). The former factors can modulate the route towards transition.…”
Section: Introductionmentioning
confidence: 99%
“…The value of Re h has an important effect on the streak amplitude, length scales and perturbation growth rate (Choudhari & Fischer 2005;Ergin & White 2006;Denissen & White 2008). The former factors can modulate the route towards transition.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest here is in studying the transient growth of the wakes behind a linear array of roughness element, which usually occurs in a region where their spanwise length scale is of the order of the local boundary layer thickness (e.g., Ergin and White, 2006) and (as will be shown below) the flow is governed by the BRE. We, therefore, consider an incompressible flat plate boundary layer that is perturbed by a spanwise periodic linear array of roughness elements at some downstream location, say (Note that we have omitted the star superscript on U  even though it denotes a dimensional quantity.)…”
Section: Formulation and Scalingmentioning
confidence: 99%
“…The solution for the roughness wake flow (which exhibits transient growth) is now governed by the nonlinear form of the BRE at the lowest order of approximation, and can, therefore, provide an appropriate base flow for studying the secondary instability and the eventual breakdown into turbulence that was noted by Ergin & White (2006). But, the second order term in the BRE solution, which is O(R 1/8 ) relative to the zeroth order solution and formally corresponds to the linear solution given in GSDC 2, turns out to be much larger than the leading order nonlinear contribution at the start of the BRE region (at least at the finite Reynolds numbers relevant to the experiments).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that, the roughness elements had no effect on the rate of transition. Ergin & White (2006) carried out an experimental study in a flat plate boundary layer downstream of a spanwise array of cylindrical roughness elements at both subcritical and supercritical values of Re k . They observed rapid transition only for Re k =334 because of the sufficiently large fluctuation growth, and they stated that the growth of unsteady disturbance increased with the increasing Re k .…”
mentioning
confidence: 99%